Optimizing Injection Moulding Processes for Structural Components in Construction Management - Qurashi, Muhammad Nasir; Xiao, Cheng-Long; Alrasheed, Khaled A.; Benjeddou, Omrane (Salehan Institute of Higher Education, 2024)
The optimization of injection molding processes for structural components is critical in construction management, particularly for enhancing precision, efficiency, and sustainability. However, existing research has not fully addressed the complex interplay of factors that influence this optimization. This study aims to fill this gap by identifying and analyzing five key constructs: Structural Performance, Material Efficiency, Sustainability and Integration, Precision and Consistency, and Design Flexibility. Data were collected from 249 professionals in China using a Likert-scale survey and analyzed through Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM). The results show that Structural Performance is the most significant factor (β = 0.943, p < 0.001), followed by Material Efficiency (β = 0.858, p < 0.001) and Sustainability and Integration (β = 0.772, p < 0.001). The model's predictive relevance, with a Q² value of 0.659, confirms its robustness and accuracy. These findings highlight the need for construction managers to focus on improving Structural Performance and Material Efficiency while integrating sustainability and ensuring precision and flexibility. Optimizing injection molding for construction components is challenging due to complex factors like structural performance, material efficiency, and sustainability. This study develops a novel framework using Structural Equation Modeling to rank these factors, providing insights for cost-effective, high-performance outcomes, and advancing sustainable practices in construction management. Doi: 10.28991/CEJ-2024-010-10-020 Full Text: PDF